Game Changers: A participatory action research project for/with students with disabilities in school sport settings - Robinson, Daniel B.; Harenberg, Sebastian; Walters, William; Barrett, Joe; Cudmore, Anna; Fahie, Kelsey; Zakaria, Tricia (Frontiers in Sports and Active Living, 2023)
Introduction Although school communities may be required to provide physical education opportunities for all students—including for those with disabilities—the same is not generally true with respect to school sport (i.e., participation in interscholastic or intramural sport programs). Hence, opportunities for inclusive school sport participation are consequently limited. Recognizing the need for continued attention and action in this area, we recently developed and piloted Game Changers—a participatory action research project. Together, 27 students with various cognitive and/or intellectual disabilities (i.e., student-participants), their schools’ six physical education teachers and learning support teachers (i.e., champion-participants), four university researchers (i.e., researcher-participants), and two community partners [i.e., Physical and Health Education (PHE) Canada, Special Olympics Nova Scotia] engaged in the Game Changers project with three idealized goals: (a) to bring to the fore para/adapted/inclusive sport opportunities for all students; (b) to provide an empowering opportunity for students with disabilities to participate, make choices, and act as leaders in the development of sport programming; and (c) to engage youth with disabilities in sport as participants, leaders, mentors, and role models. Methods Utilizing a mixed-methods design, data were collected from a variety of sources before the implementation of the Game Changers program, during its implementation, and once it was complete. These four data sources included the following: pre- and post-program survey for student-participants, pre- and post-program focus group interviews for student-participants, pre- and post-program focus group interviews for champion-participants, and school/sport observations. Results The first cycle of this participatory action research project has yielded positive and informative findings. Strictly positive findings, among others, relate to the following: improving upon students' perceived competence and autonomy, inviting student voice, identifying and responding to sport participation barriers, and creating genuine sport opportunities within school settings. More undesirable yet informative findings, among others, relate to the following: unachieved intrinsic motivation and belonging, (un)sustainability of sport programs without “interventions” like Game Changers, recreation/leisure as “substitutes” for sport, and a continued want for authentic leadership and mentorship opportunities. Discussion With these findings, we offer insights for future iterations of Game Changers (and programs like it) in similar school communities.